2015
DOI: 10.3390/nu7053536
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Selenium Compounds—From Toxicity and Cell Death to Cancer Treatment

Abstract: Selenium is generally known as an antioxidant due to its presence in selenoproteins as selenocysteine, but it is also toxic. The toxic effects of selenium are, however, strictly concentration and chemical species dependent. One class of selenium compounds is a potent inhibitor of cell growth with remarkable tumor specificity. These redox active compounds are pro-oxidative and highly cytotoxic to tumor cells and are promising candidates to be used in chemotherapy against cancer. Herein we elaborate upon the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
203
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(212 citation statements)
references
References 77 publications
3
203
1
5
Order By: Relevance
“…There exist two key metabolites of Se, which are critical for chemoprevention/ chemotherapy. 48 Hydrogen selenide necessary for the formation of selenoproteins results mainly from inorganic selenocompounds such as selenate or selenite, respectively, and methylselenol, which is generated from organic selenocompounds. In this study, the pro-oxidant MSA, a synthetic selenocompound and precursor of methylselenol, induced MHC class I surface expression not only in B16F10 melanoma cells, but also on several other tumor cell lines, including human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…There exist two key metabolites of Se, which are critical for chemoprevention/ chemotherapy. 48 Hydrogen selenide necessary for the formation of selenoproteins results mainly from inorganic selenocompounds such as selenate or selenite, respectively, and methylselenol, which is generated from organic selenocompounds. In this study, the pro-oxidant MSA, a synthetic selenocompound and precursor of methylselenol, induced MHC class I surface expression not only in B16F10 melanoma cells, but also on several other tumor cell lines, including human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Today, it is generally admitted that oxidative stress is a determinant factor of selenium cytotoxicity as well as anticarcinogenic properties (17,64). Pro-oxidant properties of selenium originate from the in vivo conversion of seleno-compounds into H 2 Se or into selenols (RSeH: SeCys, MeSe, GSeH,…), which are readily oxidized by oxygen with concomitant generation of ROS (Figure 2A and B) (9,(65)(66)(67)(68).…”
Section: Selenium and Oxidative Stressmentioning
confidence: 99%
“…Because cancer cells generally exhibit an increased vulnerability to ROS-producing compounds, there is an increasing interest in designing anticancer agents promoting oxidative stress. Among redox active drugs, selenite is a promising candidate as a cancer therapeutic agent (17,151). The next step consists in evaluating its toxicity in cancer patients and the therapeutic potential of redoxactive selenium compounds.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic selenium (sodium selenite) has been found to prevent oxidative stress caused by methamphetamine in neuronal cells [5] and by As 2 O 3 in fish hepatoma cells [6], as well as t-butyl hydroperoxide-induced DNA damage in human mesenchymal stromal cells [7]. Other forms (organic compounds and nanoparticles) of selenium have also been studied and the research has revealed the dependence of the effects on the used form [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%